PSYCHOLOGICAL PECULIARITIES OF HIGHER EDUCATION IN THE REPUBLIC OF ARMENIA AND OTHER COUNTRIES - Poghosyan, S. H.; Mesrobyan, V. A. (Modern Psychology, 2025)
The article presents the psychological peculiarities of higher education in different countries. The aim of the article is to present the psychological peculiari- ties of higher education in different countries. The aim of this article is to study the psychological peculiarities of education in management, to reveal the differen- ces and commonalities of the educational systems of different countries. We have chosen comparison as a method, and as criteria of comparison we have singled out the level of higher education, the duration of study and the professional- psychological qualities of the lecturer. Such a study will provide an opportunity to identify the professional-psychological qualities of lecturers from different coun- tries, on the basis of which we can compile a psychological portrait of a lecturer.
Keywords: higher education, different countries, educational system, psychological peculiarity, differences, commonalities.